2021
DOI: 10.48550/arxiv.2110.09565
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Fractional Chern insulators with a non-Landau level continuum limit

David Bauer,
Spenser Talkington,
Fenner Harper
et al.

Abstract: Recent developments in fractional quantum Hall (FQH) physics highlight the importance of studying FQH phases of particles partially occupying energy bands that are not Landau levels. FQH phases in the regime of strong lattice effects, called fractional Chern insulators, provide one setting for such studies. As the strength of lattice effects vanishes, the bands of generic lattice models asymptotically approach Landau levels. In this article, we construct lattice models for single-particle bands that are distin… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 80 publications
1
4
0
Order By: Relevance
“…We provided deformations of the Berry curvature and quantum metric upon applying a small magnetic field and went on investigating the properties of this new quantum geometry in the insulating and metallic regime. We point out that our work is to be distinguished from recent advances implementing strong magnetic fields which push the system into the Hofstadter phase [13,14]. In the insulating regime, we showed that the Hall conductivity is not affected by small magnetic fields, in agreement with previous work.…”
Section: A Conclusionsupporting
confidence: 91%
See 4 more Smart Citations
“…We provided deformations of the Berry curvature and quantum metric upon applying a small magnetic field and went on investigating the properties of this new quantum geometry in the insulating and metallic regime. We point out that our work is to be distinguished from recent advances implementing strong magnetic fields which push the system into the Hofstadter phase [13,14]. In the insulating regime, we showed that the Hall conductivity is not affected by small magnetic fields, in agreement with previous work.…”
Section: A Conclusionsupporting
confidence: 91%
“…Our work dealt exclusively with properties of ideal bands and it is an interesting future endeavor to study the consequences of our work once interactions are implemented on the band. This is similar in spirit, yet significantly different from [14], which presents as well a study of fractional Chern insulators in magnetic fields. Our work differs from theirs, since they employed strong magnetic fields B allowing them to use magnetic Brillouin zones and work entirely with its quantum geometry.…”
Section: B Outlookmentioning
confidence: 73%
See 3 more Smart Citations